2018
DOI: 10.1111/eip.12542
|View full text |Cite
|
Sign up to set email alerts
|

Impact of tobacco, alcohol and cannabis use on treatment outcomes among patients experiencing first episode psychosis: Data from the national RAISE‐ETP study

Abstract: Tobacco, alcohol and cannabis use are common in youth seeking treatment for FEP. Tobacco smoking was associated with more negative clinical outcomes. These findings have implications for including interventions targeting these areas of substance use within current CSC models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 24 publications
8
36
0
1
Order By: Relevance
“…In addition, cannabis users showed more severe positive symptoms and general severity of psychopathology (higher scores on the BPRS) at baseline. These findings are in line with previous research where consumers were characterized by presenting more serious symptoms. This would indicate that since the beginning of the illness, the severity of symptoms is greater in the group of patients who use cannabis, which allows for several interpretations.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, cannabis users showed more severe positive symptoms and general severity of psychopathology (higher scores on the BPRS) at baseline. These findings are in line with previous research where consumers were characterized by presenting more serious symptoms. This would indicate that since the beginning of the illness, the severity of symptoms is greater in the group of patients who use cannabis, which allows for several interpretations.…”
Section: Discussionsupporting
confidence: 93%
“…These findings should be interpreted with caution as we did not find a further significant effect using regression modeling. Nevertheless, the connection between cannabis use and positive psychotic symptoms has been previously found 42,43 although this relationship is unclear. 44,45 To our knowledge, the finding that EPP patients who use alcohol only may express fewer positive symptoms at entry to care is novel.…”
Section: Discussionmentioning
confidence: 96%
“…Unhealthy lifestyle behaviors may impact mental health and suicidal behavior by influencing emotions and judgement. Studies have demonstrated that adolescents with first-episode psychosis have a high prevalence of tobacco, alcohol and cannabis use, selective dietary habits, lower physical activity, and lower level of activity during leisure time ( 27 30 ). Other studies have demonstrated a close relationship between cannabis use, hypomania, mania, and suicide risk in adolescents ( 31 , 32 ).…”
Section: Lifestyle Behavior and Suicide In Adolescents And Young Peopmentioning
confidence: 99%